1987
DOI: 10.1002/jcp.1041320317
|View full text |Cite
|
Sign up to set email alerts
|

Production of tumor growth‐inhibiting protein by the neonatal mouse brain: Dependence on intracellular glutamine metabolism

Abstract: We previously reported that the mouse brain at the neonatal stage but not at the adult stage secreted a carcinostatic factor of 62,000 Da, termed NBCF, which inhibited clonal growth and DNA synthesis of malignant cells preferentially over those of normal cells. In the present study, NBCF production by the neonatal mouse brain in culture was investigated. Addition of L-glutamine to the culture medium markedly promoted NBCF production in a concentration-dependent manner. The production seemed to be specific to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1990
1990

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Using an astroglial proliferation assay that has a high signal-to-noise ratio, we demonstrated that neurons release a protein that downregulates astroglia proliferation. The neuronal downregulation of astroglial prolifer-tumour growth-inhibitory protein of about 62 kDa found in neonatal mouse brain extracts (Miwa et al, 1987). The cellular origin, the spectrum of targets cells, and thc molecular weight of these factors are different from those found for astrostatine.…”
Section: Discussionmentioning
confidence: 86%
“…Using an astroglial proliferation assay that has a high signal-to-noise ratio, we demonstrated that neurons release a protein that downregulates astroglia proliferation. The neuronal downregulation of astroglial prolifer-tumour growth-inhibitory protein of about 62 kDa found in neonatal mouse brain extracts (Miwa et al, 1987). The cellular origin, the spectrum of targets cells, and thc molecular weight of these factors are different from those found for astrostatine.…”
Section: Discussionmentioning
confidence: 86%